Integration of Literacy Strategies in Teaching Science among Grade IV Pupils of Zone II Zambales Division for The School Year 2019 – 2020 - Sebastian, Mary Jane A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study aimed to assess and determine the integration of literacy strategies in teaching Science among Grade IV elementary pupils of Zone II Division of Zambales during the School Year 2019-2020. The researcher utilized the descriptive research design with questionnaire as the main instrument in gathering data and information from (50) Science teachers and determine their profile as to age, sex, highest educational attainment, position, and numbers of years in teaching Science. The study was limited to determine perception towards integrating literacy in teaching Science among elementary pupils as to Paraphrasing/Vocabulary Instruction, Summarizing Science, Interactive Read-Aloud, Interactive Reading Guides, and Writing A Scientific Explanation The result of the study revealed that most of the respondents are from age-group of 30-39 with 19 or equivalent to 38.00% and with mean age of 38.1 years old; majority of the respondents are female teachers with 29 or equivalent to 58.00%; majority have attained Masteral units and with 27 or equivalent to 54.00%; mostly are occupying Teacher I and with 19 or equivalent to 38.00%; and 18 or equivalent to 36.00% are in the teaching service for 6-9 years with mean of 7.6% or 8 years in the service. Based on the summary of the investigations conducted, the researcher has arrived to conclude that the respondent is a typical female in her middle adulthood, Teacher 1, with Masteral units and has served for almost a decade in the teaching service. The respondents Highly Practiced Paraphrasing/Vocabulary Instruction, Summarizing Science, Interactive Read-Aloud, Interactive Reading Guides, and Writing A Scientific Explanation. The students were assessed “Average Mastery” in their academic performance. Based on the summary of the investigations conducted and the conclusions arrived at the researcher has offered the following recommendations based on the salient findings obtained in the study. It is encouraged that the Science teachers have to finish their Masteral Degree for them to have higher academic rank. The Science teachers have to sustain the teaching strategies in Paraphrasing, Summarizing in Science, Interactive Read Aloud, Interactive Reading Guides, and Writing Scientific Explanation must be sustained among science teachers. The teachers have to encourage pupils to develop study habits to improve the academic performance. Teachers are encouraged to be sensitive and vigilant to pupils who are passive in the subjects and make them highly involve in all activities by giving rewards and recognition. If budget warrants, provision of internet services in classroom environment is strongly recommendable for better appreciation and learning Science. The future researchers have to conduct a parallel or similar study with in-depth and wider in scope so as to validate and confirm the findings obtained in the study.